Substantial mitigation of nitrous oxide realized in a light-mediated and aeration-free microalgal-bacterial consortium system - Lingfeng Wang; Weican Shi; Yanlin Liu; Zhaoming He; Jianhua Guo; Shijian Ge; Shuang Qiu (Algal Research, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Dynamic characterization of representative naval steels under high-velocity fragment impact and functional vulnerability assessment of naval propulsion-system components - WenCai Sun; HouXiang Wang; LingFeng Hu; YuAng Shi; JianNan Li; ZiChun Yang (Ocean Engineering, 2026)

Influence of substrate on emplacement of a large rock avalanche in the west-central Tibetan Plateau, China: Insights from geomorphology and sedimentology - AnWen Shi; Yongbo Tie; YuFeng Wang; QianGong Cheng; HaoRan Tian; Lingfeng Gong; XiaoHui Xiong (Geomorphology, 2026)

Environmental changes in the Okinawa Trough over the last 88 ka BP: Evidence from high-resolution bulk mineralogy - Lingfeng Luo; Xuguang Feng; Jianjun Zou; Xisheng Fang; Xinru Xue; Ruxi Dou; Baohua Han; Qingchao Wang; Aimei Zhu; Zhi Dong; Gang Yang; Xuefa Shi (Marine Geology, 2026)

Community assembly and nitrogen metabolic characteristics of size-fractionated microorganisms in floating bed restoration area - Yi Shi; Rui Zhao; Lingfeng Huang; Wenjing Zhang (Journal of Oceanology and Limnology, 2026)

Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

Nano-magnetoelectric biomimetic system promotes neural differentiation and reverses dopaminergic neuron damage for Parkinson's disease therapy - Jie Zhang; Jiahui Shi; Qiubo Yang; Haogang Guo; Lingfeng Guo; Guoliang Zhou; Yinyi Liu; Xiaolei Wang; Xian Hao; Yifei Yang (Chemical Engineering Journal, 2025)

In-situ atmospheric thermoelectric conversion on Mars - Yuzhuo Yang; Yonghao Zhang; Yu Yao; Gang Pei; Hua Tian; Lingfeng Shi; Gequn Shu (Science Bulletin, 2025)

Improving the efficiency of a CO2 heat pump for simultaneous heating and cooling coupled with an ambient source - Zhaoyang Yuan; Jintao He; Yonghao Zhang; Yu Yao; Hua Tian; Lingfeng Shi; Gequn Shu (International Journal of Refrigeration, 2025)

A hybrid cooling and power cogeneration scheme for broadening adaptability to distributed buildings: conceptual design, modeling, and operational assessment - Yonghao Zhang; Lingfeng Shi; Hua Tian; Jintao He; Yu Yao; Gequn Shu (Energy and Buildings, 2025)

Pressure-driven high-capacity lithium-carbon dioxide batteries - Tenghui Qiu; Xu Xiao; Zhuojun Zhang; Zehui Zhao; Aijing Yan; Yasen Hao; Lingfeng Shi; Peng Tan; Gequn Shu (Chemical Engineering Journal, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

A robust index was extracted to assess the prolonged changes in debris flow activity after a high magnitude earthquake - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Jiangang Chen; Tao Yang; Lingfeng Gong; Ming Chen; Qingyun Shi; Ning Li (CATENA, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Response of nitrifiers to gradually increasing pH conditions in a membrane nitrification bioreactor: Microbial dynamics and alkali-resistant mechanism - Weican Shi; Zhaoming He; Jiahui Lu; Lingfeng Wang; Jianhua Guo; Shuang Qiu; Shijian Ge (Water Research, 2025)

Abrupt enhanced Pacific warm water intrusion into the Sea of Okhotsk since the early Holocene - Xuguang Feng; Jianjun Zou; Xuefa Shi; Zhengquan Yao; Zhi Dong; Jiang Dong; Yonghua Wu; Ruxi Dou; Hualong Jin; Aimei Zhu; Xiaojing Wang; Qingchao Wang; et al. (Quaternary Science Reviews, 2024)

Mapping critical soil moisture thresholds of water stress for global grasslands - Lingfeng Shi; Yanlian Zhou; Wei He; Zhoutong Dong; Zhuoyou Jiang; Yuyan Wang; Yibo Liu; Weimin Ju; Zheng Duan (Journal of Hydrology, 2024)

Bioorthogonal surface-edited exosomes for targeted multimodal imaging and synergic chemophototherapy of oral cancer - Yuxiao Wu; Xiaofeng Shan; Yuanjie Zhang; Wen Shi; Xingxing Zhu; Mengfan Yu; Shang Xie; Lingfeng Guo; Zhiqian Chen; Chuanling Zhang; Demin Zhou; Zhigang Cai (Chemical Engineering Journal, 2024)

Hormone and reproductive factors and risk of systemic lupus erythematosus: a Mendelian randomized study - Runyu Chang; Shate Xiang; Yibo Jin; Xiaofen Xu; Suhai Qian; Lingfeng Chen; Chao Hu; Yufeng Shi; Xinghong Ding (Immunologic Research, 2024)

Potential high-risk release sources of thallium and arsenic from surrounding rocks of a typical thallium and arsenic mining area in southwest China - Yanpei Du; Lingfeng Shi; Xinyan Cao; Fengqi Zhao; Pengjie Hu; Rongrong Ying; Shangyi Gu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Doped microspheres for whispering gallery mode microlasing - Xiaoxuan Wang; Chaoyang Huang; Chuansheng Xia; Feifei Qin; Gangyi Zhu; Lingfeng Mao; Yi Ma; Zengliang Shi; Qiannan Cui; Chunxiang Xu (Science Bulletin, 2024)

Physiological and transcriptomic analysis revealed that the accumulation of reactive oxygen species caused the low temperature sensitivity of Liriodendron × sinoamericanum - Ye Lu; Lingfeng Hu; Long Yu; Shuang Liang; Haoxian Qu; Mingqi Wang; Zhaodong Hao; Liming Yang; Jisen Shi; Jinhui Chen (Plant Science, 2024)

Impact of hypoxia on glucose metabolism and hypoxia signaling pathways in juvenile horseshoe crabs Tachypleus tridentatus - Lingfeng Jiang; Yueyong Shang; Yuntian Shi; Xiaowan Ma; Malik ShahZaib Khalid; Meilian Huang; James Kar-Hei Fang; Youji Wang; Kianann Tan; Menghong Hu (Marine Environmental Research, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Responses of microeukaryotic community structure to a Phaeocystis globosa bloom in a semi-enclosed subtropical bay - Beibei Han; Rongjun Shi; Shufei Zhang; Anji Lian; Zexing Kuang; Fengxia Wu; Lingfeng Huang; Honghui Huang (Marine Environmental Research, 2024)

Potential mobilization of water-dispersible colloidal thallium and arsenic in contaminated soils and sediments in mining areas of southwest China - Yanpei Du; Lingfeng Shi; Xinyang Li; Juan Liu; Rongrong Ying; Pengjie Hu; Longhua Wu; Peter Christie (Journal of Hazardous Materials, 2024)

Water-dispersible colloids facilitate the release of potentially toxic elements from contaminated soil under simulated long-term acid rain - Juan Liu; Lingfeng Shi; Yanpei Du; Xueting Luo; Pengjie Hu; Longhua Wu; Yongming Luo; Peter Christie (Science of The Total Environment, 2024)

Vapor-liquid equilibrium measurement for carbon dioxide (CO2)+propylene (R1270) binary mixture at temperatures from subcritical to supercritical - Zirui Wu; Rui Sun; Lingfeng Shi; Peng Hu; Hua Tian; Xuan Wang; Gequn Shu (International Journal of Refrigeration, 2024)

Saving the overlooked mangrove horseshoe crabs-A perspective from enhancing mangrove ecosystem conservation - Yuntian Shi; Shuhui Li; Yaowu Li; Lingfeng Jiang; Fahim Ullah Khan; Khor Waiho; Youji Wang; Menghong Hu (Marine Environmental Research, 2024)

Improving the long-term performance of electric vehicles CO2 heat pump through correcting discharge pressure - Yuzhuo Yang; Lingfeng Shi; Hua Tian; Gequn Shu (Journal of Cleaner Production, 2024)

A low-carbon CO2 ice rink technology for the Winter Olympics - Ligeng Li; Kai Liu; Hua Tian; Jinwen Cai; Christos N Markides; Jingyu Wang; Lingfeng Shi; Xuan Wang; Yitai Ma; Xingyu Liang; Gequn Shu (Science Bulletin, 2023)

Revealing the specificity of map method to predict the performance of a combined cooling and power cycle under operating conditions - Yu Yao; Lingfeng Shi; Jintao He; Xiaocun Sun; Bowen Lu; Yonghao Zhang; Hua Tian; Xuan Wang; Gequn Shu (Journal of Cleaner Production, 2023)

Application of remote sensing monitoring to the spatiotemporal variation in debris flow activity in the catastrophic Wenchuan seismic area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Ming Chang; Xianzheng Zhang; Lingfeng Gong; Ning Li; Qingyun Shi; Mingwei Li (CATENA, 2023)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Fast satellite selection algorithm for GNSS multi-system based on Sherman–Morrison formula - Junpeng Shi; Kezhao Li; Lin Chai; Lingfeng Liang; Chendong Tian; Keke Xu (GPS Solutions, 2023)
Efficient use of global navigation satellite system (GNSS) observations improves when applying rational satellite selection algorithms. By combining the Sherman–Morrison formula and singular value decomposition, a smaller-GDOP (geometric dilution of precision)-value method is proven for an increasing number of visible satellites. By combining this smaller-GDOP-value method with the maximum-volume-tetrahedron method, a new rapid satellite selection algorithm based on the Sherman–Morrison formula for GNSS multi-systems is proposed. The basic idea of the algorithm is as follows: First, the maximum-volume-tetrahedron method is used to obtain four initial visible satellites. Then, the other visible satellites are selected by using the smaller-GDOP-value method to reduce the GDOP value and improve the accuracy of the overall algorithm. When the number of included satellites reaches a certain value, the rate of GDOP decrease tends to approach zero. Considering the algorithm precision and the computation efficiency, reasonable thresholds and end of calculation condition equation are given, which can make the proposed algorithm autonomous. The reasonable thresholds and the end of calculation parameters are suggested by means of experiments. Under the thresholds and the end of calculation parameters, the algorithm has an adaptive functionality. Furthermore, the GDOP values of the algorithm are less than 2, indicating that this algorithm can meet one of the requirements of high-precision navigation. Moreover, compared with the computation complexity values of the optimal GDOP estimation method, which includes all visible satellites, the values of the new algorithm are about half, indicating that this algorithm has a rapid performance. These findings verify that the proposed satellite selection algorithm based on the Sherman–Morrison formula provides autonomous functionality, high-performance computing, and high-accuracy results.

Ecosystem Services of Ecosystem Approach to Mariculture: Providing an Unprecedented Opportunity for the Reform of China’s Sustainable Aquaculture - Xijie Zhou; Jinghui Fang; Siyuan Shi; Ling Yang; Bin Xie; Lingfeng Huang (Frontiers in Marine Science, 2022)
China is the biggest provider of mariculture products, and the industry is still growing rapidly. Increasing scientific evidence indicates that mariculture may provide valuable ecosystem goods and services in China. Here, we performed a systematic literature review of studies with the aim of understanding the ecosystem services of mariculture and a comprehensive review of ecosystem approaches that may improve mariculture ecosystem services and goods in China. We highlight four ecosystem services functions in China, including food supply, nutrient extraction, carbon sequestration, and biodiversity conservation. Given the further reform of China’s mariculture, we outlined several ecosystem approaches including integrated multi-trophic aquaculture (IMTA), carrying capacity assessment and monitoring, marine spatial planning, and waste treatment and recirculating mariculture system. We conclude that the ecosystem services of the ecosystem approach to mariculture provide an unprecedented opportunity for the reform of China’s sustainable aquaculture. Finally, a synthesis of sustainable development of mariculture, along with the five recommendations for future mariculture development in China, is outlined.

Activity characteristics and enlightenment of the debris flow triggered by the rainstorm on 20 August 2019 in Wenchuan County, China - Jiang Xiong; Chuan Tang; Ming Chen; Xianzheng Zhang; Qingyun Shi; Lingfeng Gong (Bulletin of Engineering Geology and the Environment, 2021)

Impedimetric biosensor fabricated with affinity peptides for sensitive detection of Escherichia coli O157:H7 - Fan Shi; Lingfeng Gan; Yibing Wang; Ping Wang (Biotechnology Letters, 2020)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)